Wellbeing Economics The Capabilities Approach to Prosperity - Dalziel, Paul.; Saunders, Caroline; Saunders, Joe.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2018)
Economists have long sought to maximise economic growth, believing this to be their best contribution to improving human welfare. That approach is not sustainable in the face of ongoing issues such as global climate change, environmental damage, rising inequality and enduring poverty. Alternatives must be found. This open access book addresses that challenge. It sets out a wellbeing economics framework that directly addresses fundamental issues affecting wellbeing outcomes. Drawing inspiration from the capabilities approach of Nobel Prize winner Amartya Sen, the book demonstrates how persons can enhance prosperity through their own actions and through collaboration with others. The book examines national public policy, but its analysis also focuses on choices made by individuals, households, families, civil society, local government and the global community. It therefore offers important insights for anyone concerned with improving personal wellbeing and community prosperity. Paul Dalziel is Professor of Economics and Deputy Director of the Agribusiness and Economics Research Unit at Lincoln University, New Zealand. Caroline Saunders is Professor of Trade and Environmental Economics and Director of the Agribusiness and Economics Research Unit at Lincoln University, New Zealand. Joe Saunders is Assistant Professor in Post-Kantian Philosophy at the University of Durham, UK.
Chapter 1: From Economic Growth to Wellbeing Economics -- Chapter 2: Persons and Human Capital -- Chapter 3: Households, Families and Cultural Capital -- Chapter 4: Civil Society and Social Capital -- Chapter 5: Market Participation and Economic Capital -- Chapter 6: Local Government and Natural Capital -- Chapter 7: The Nation State and Knowledge Capital -- Chapter 8: The Global Community and Diplomatic Capital -- Chapter 9: The Wellbeing Economics Policy Framework.
Keywords: Social choice; Welfare economics; Political planning; Political science; Economic policy; Economic development; Social Choice and Welfare; Public Policy; Governance and Government; Economic Policy; Economic Growth